Multidecadal climate‐induced changes in Arctic tundra lake geochemistry and geomorphology - Travis W. Drake; Robert M. Holmes; Alexander V. Zhulidov; Tatiana Gurtovaya; Peter A. Raymond; James W. McClelland; Robert G. M. Spencer (Limnology and Oceanography, 2019)
High‐latitude lakes are sensitive indicators of climate and important ecological components of Northern landscapes. The response of Arctic lakes to accelerated 20 th century warming has largely been inferred from paleolimnological and shorter‐term observational studies ( p CO 2 , measured during the ice‐free period in late summer, increased over time. Over the same period, the rates of primary and bacterial production increased significantly. Permafrost thaw at the base and margins of the lakes likely resulted in the observed increase in size, as measured by average depth, surface area, and total volume. The observed changes show strong correlation with temperature, suggesting an overall pronounced response to warming. Importantly, CO 2 sourced from either in situ or allochthonous respiration of thawed permafrost would indicate the destabilization of a large C reservoir.